Challenges in Managing an Ischemic Stroke in a Child with Homozygous SS Sickle Cell Disease Associated with Cerebral Palsy: A Case Report - Amon Tanoh, Muriel; Boundjike, Rosette; Tanya De-Souza, Nancy; Valery Kadjo, Cedric; Kone, Mody; Yapo-Ehounoud, Constance; Diakite, Ismaila; Tanoh, Christian; Aka Diarra, Evelyne; Assi, Berthe (European Scientific Journal, ESJ, 2025)
Introduction: Ischemic stroke is one of the most frequent complications of sickle cell disease (SCD) and may be associated with cognitive impairment. These two neurological manifestations can coexist in the same patient. Objective: To report a case of ischemic stroke and cognitive delay in a child with homozygous SS sickle cell disease. Case Report: We describe a 5-year and 8-month-old boy with homozygous SS sickle cell disease and epilepsy, non-compliant with his antiepileptic treatment, admitted for seizures that had progressively worsened over two months. A diagnosis of complicated major sickle cell syndrome was made. Discussion: The management of neurovascular, epileptic, and cognitive complications in this patient with cerebral palsy and sickle cell disease required evaluating the risk of severe anemia and stratifying the likelihood of stroke recurrence. Conclusion: Managing major sickle cell syndrome associated with neurovascular, epileptic, and cognitive complications in a child with cerebral palsy requires adherence to current evidence-based recommendations.